2015
DOI: 10.1186/s12889-015-1490-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related factors influencing the occurrence of undernutrition in northeastern Ethiopia

Abstract: BackgroundUndernutrition is a major public health problem on the globe particularly in the developing regions. The objective of the current study was to assess the prevalence of undernutrition in different age groups and examine the relationship of the disease to parasitic and socioeconomic factors among communities in Harbu Town, northeastern Ethiopia.MethodsStool samples of the study participants were examined for intestinal helminth infections using the Kato-Katz method. Blood specimens were diagnosed for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
7
20
3
Order By: Relevance
“…Despite a well-documented link between soil-transmitted helminth infections and undernutrition (58, 59), the evidence regarding this association varies. Some studies have reported the same risk of wasting and stunting among infected and non-infected children (11, 60, 61). In agreement with other studies (62, 63), our study revealed higher rates of intestinal parasites among wasted children.…”
Section: Discussionmentioning
confidence: 94%
“…Despite a well-documented link between soil-transmitted helminth infections and undernutrition (58, 59), the evidence regarding this association varies. Some studies have reported the same risk of wasting and stunting among infected and non-infected children (11, 60, 61). In agreement with other studies (62, 63), our study revealed higher rates of intestinal parasites among wasted children.…”
Section: Discussionmentioning
confidence: 94%
“…This supports the notion that A. lumbricoides may have molecules that resemble the antigen of blood type A, or that the parasite may adsorb blood type A antigens. Previous studies have also documented high prevalence or intensity of S. mansoni infection in children with blood type A (Ndamba et al, 1997;Degarege et al, 2015). This will help the parasites to survive and multiply easily within the host, causing severe intestinal damage and high blood loss.…”
Section: Discussionmentioning
confidence: 96%
“…Children whose families were educated and consisted of fewer than five family members had significantly lower odds of undernutrition compared with peers in illiterate families and family sizes of more than five members, respectively 26 ) . Independent of household wealth, a lower paternal and maternal education level was also associated with child stunting 27 ) .…”
Section: Discussionmentioning
confidence: 98%